The Relationship Between Supplementation and Sport - Gréta Újvári; Brigitta Zsótér; Zoltán Veres (Analecta)
Nowadays, the fitness industry has become a growing industry alongside the nutritional supplements industry within the food industry. Small and large companies are fighting for consumers. They offer products tailored to different training goals, whether sold online or offline. Companies are developing their marketing strategies by observing consumer preferences and habits. But do we need supplementation? Are the products on the market safe? What do we even mean by a food supplement? Is it a good idea to buy supplements that are in line with the latest trends? In this study we will show whether or not supplementation is really necessary for athletes and what determines whether it is.